IMPLEMENTASI TUGAS POKOK DAN FUNGSI PENGAWAS MADRASAH DALAM PENINGKATAN MUTU MADRASAH ALIYAH SE-KECAMATAN TANETE RIATTANG KABUPATEN BONE - Erwin, Erwin; Usman, Syahruddin; Ibrahim, Misykat Malik (Idaarah: Jurnal Manajemen Pendidikan, 2020)
The problem of this research is on the roles and functions of madrasah supervisors in improving the quality of Madrasah Aliyah in Tanete Riattang district of Bone regency. It’s important to know the understanding of supervisors on their roles and functions in improving the quality of schools, the planning of supervisors in conducting their roles and functions, and the implementation of supervision in improving the quality of Madrasah Aliyah in Tanete Riattang district of Bone regency. This reseach was a qualitative research where the main sources of the research data were the head of the Ministry of Religious Affairs of Bone, Madrasah supervisors, Principals, teachers, and staffs of Madrasah Aliyah in Tanete Riattang district. Data processing and analysis techniques were carried out through three stages of data reduction, data display, and data conclusion drawing. The results of this research showed that the supervisors’ understanding was monotonous in which the supervisors prepared their programs according to the supervisory standard. In addition, the supervisors merely made a one-time visit to 24 different madrasas which could be considered to be inefffective.